2017
DOI: 10.1021/acs.joc.7b00537
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Conformational and Chemical Transformations of Ortho-Substituted Aromatic Nitroso Oxides: Experimental and Theoretical Study

Abstract: The mechanism of the photooxidation of aromatic azides containing a substituent at one of the ortho positions (2,4-dimethoxyphenyl azide (1a) and 2-methyl-4-[(2E)-1-methylbut-2-en-1-yl]phenyl azide (1b)) was studied in acetonitrile. The electronic spectra and the kinetic regularities of the consumption of corresponding nitroso oxides, which are the reaction intermediates, were investigated by flash photolysis. Owing to the one-and-a-half order of the C-N and N-O bonds and asymmetric molecule structure these ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Second, it was found that the presence of a substituent at the ortho position facilitates the ortho-cyclization. Thus, under the photooxidation of 2,4-dimethoxyphenyl azide, a nitrile oxide, which was formed as a result of the reaction of the nitroso oxide group with the substituted ortho -carbon atom, was obtained as the sole product . The effect of an ortho substituent was studied in detail using density functional theory calculations .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, it was found that the presence of a substituent at the ortho position facilitates the ortho-cyclization. Thus, under the photooxidation of 2,4-dimethoxyphenyl azide, a nitrile oxide, which was formed as a result of the reaction of the nitroso oxide group with the substituted ortho -carbon atom, was obtained as the sole product . The effect of an ortho substituent was studied in detail using density functional theory calculations .…”
Section: Discussionmentioning
confidence: 99%
“…Nitrile oxides of common structure 4 are stable enough, and they were isolated and identified during the photooxidation of 4-methoxyphenyl azide and 2,4-dimethoxyphenyl azide . In other cases, a number of carbocyclic and heterocyclic compounds , were obtained by the photooxidation of aromatic azides.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations